Sweden : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper examines the labor market and migration in Sweden. Sweden enjoys a broadly well-functioning labor market. The labor force has been expanding at a healthy pace, in part reflecting rising participation including by females. This paper discusses the compositional changes in the labor force, employment, and unemployment over the past decade. A brief overview of migration flows, their composition, and their demographic benefits is provided. An assessment of the potential implications of the projected increase in migration for unemployment is done. The features of Sweden's labor market that contribute to the higher unemployment rates of the lower skilled and foreign-born are also outlined.